ANALISA URUTAN FAKTOR PENGUJIAN SEPEDA MOTOR LISTRIK 3.000 WATT MENGGUNAKAN METODE TAGUCHI - Daniel Janthinus Kristianto; Genia Auberta; Muslimin; M. Prasha Risfi Silitonga; Wan Mansor Bin Wan Muhamad; Muhammad Aziz (MBI, 2023)
Electric vehicle manufacturers have a significant need for brushless DC (BLDC) motors. This is because of its benefits, including brushless construction, high efficiency and power ratio, huge mass, and ease of control. This study aims to examine the relative importance of the various variables on the three motorcycles that the three prototypes are actually mounted on. In order to optimize the technical testing process and save wasteful time and expense, the Taguchi Method with the characteristic of smaller is better was employed for the research. Two different types of road terrain were used for the tests: flat and uphill with slope angles of 2 and 4. Use. Prototypes 1, 2, and 3 of the electric motors utilized in this study each feature a distinct ratio of magnetic poles: prototype 1 has 48 poles/54 slots, prototypes 2 has 50 poles/45 slots, and prototype 3 has 40 poles/36 slots. According to the test results, the type of electric motor, the type of road, the distance, and ultimately the speed level are the parameters that have the greatest influence.